1996
DOI: 10.1097/00004647-199601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Absence Seizures Induce a Decrease in Cerebral Blood Flow: Human and Animal Data

Abstract: Our previous studies on cerebral metabolic activity in genetic absence epilepsy rats from Strasbourg (GAERS) were in favor of decreased functional activity during absences and normal or increased interictal activity. To ascertain that hypothesis, in the present study we performed continuous measurements of CBF in both children with typical absence epilepsy and GAERS, using Doppler ultrasonography and laser-Doppler flowmetry, respectively. CBF fluctuations during absences were recorded in four children between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
35
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
(20 reference statements)
7
35
2
Order By: Relevance
“…In GSW however we have little prior anatomical hypothosis regarding the spatial extent of BOLD changes. We propose that thalamic activation seen here represents subcortical activity , 1988,Klingelhofer et al, 1991,Bode, 1992,Nehlig et al, 1996,De Simone et al, 1998 Although the majority of our cases showed cortical negative response a number of cases showed activation or biphasic time courses in the same areas. These did not differ significantly (2-sample t-tests, all p > 0.8) from those with negative response in terms of the frequency of GSW, the number of events, their median duration or total duration during the scan session.…”
Section: Discussionmentioning
confidence: 64%
“…In GSW however we have little prior anatomical hypothosis regarding the spatial extent of BOLD changes. We propose that thalamic activation seen here represents subcortical activity , 1988,Klingelhofer et al, 1991,Bode, 1992,Nehlig et al, 1996,De Simone et al, 1998 Although the majority of our cases showed cortical negative response a number of cases showed activation or biphasic time courses in the same areas. These did not differ significantly (2-sample t-tests, all p > 0.8) from those with negative response in terms of the frequency of GSW, the number of events, their median duration or total duration during the scan session.…”
Section: Discussionmentioning
confidence: 64%
“…In four children with absences, Nehlig et al (15) documented an average CBFV decrease of 24% with a latency of 5 s during 31s gSW (two to nine paroxysms each). Most investigators (12,13,15) did not use heart-cycle integration to account for systolic and diastolic fluctuation of CBFV. By applying heart-cycle integration, a higher temporal resolution of CBFV changes can be achieved than by low-pass filtering.…”
Section: Discussionmentioning
confidence: 97%
“…In genetic absence rats of Strasbourg, petit mal status was provoked by injection of haldol; 5-10 min later, Pco, decreased. But the authors also observed a decrease in PCO, after administration of ESM, which suppressed the SW discharges (15) and therefore considered it unlikely that the reduction in perfusion during gSW was due to Pco, decrease. However, in the patient monitored for end-expiratory Pco,, we demonstrated an increase in respiratory frequency with a subsequent decrease in Pco, during gSW.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Human and animal studies have shown large increases in neuronal activity, CBF, and metabolism during GTCS (reviewed in . However, some investigators have shown increases in CBF during SWD (Prevett et al, 1995;Yeni et al, 2000), whereas others have shown the opposite (Bode, 1992;Nehlig et al, 1996;Sanada et al, 1988;Sperling and Skolnick, 1995).…”
mentioning
confidence: 98%